WordPress 24-hour trainer - Plumley, George (Wrox, a Wiley brand, 2015)
The easy, self-paced guide to the powerful WordPress platform WordPress 24-Hour Trainer, 3rd Edition provides a comprehensive, unique book-and-video package that focuses on the practical, everyday tasks you will face when creating and maintaining WordPress websites. This easy-to-use, friendly guide will show you how to create and edit pages, integrate your site with social media, keep your site secure, make content more search engine friendly to help drive website traffic, troubleshoot the most common WordPress issues, and much more.